The role of Islamic education teachers in fostering students’ emotional intelligence - Dwi Agus Kurniawan; Alimni Alimni; Alfauzan Amin (International Journal of Evaluation and Research in Education (IJERE), 2022)
This research aimed to find out how the role of Islamic Education teachers in fostering students' emotional intelligence, especially in Bengkulu City Elementary Schools. This was mixed-method research using explanatory techniques. Instruments in this study included questionnaires and interviews, with the sample were teachers and elementary school students. The strategy used by Islamic Religious Education (Pendidikan agama Islam/PAI) teachers in order to improve emotional intelligence is to focus more on student activity and attitudes, as well as by carrying out activities such as regular recitations every Friday, evening prayers, reading dhikr, and fasting to improve students' spiritual intelligence. After inviting students to do positive things such as reading history books, stories and other books that can foster motivation, doing social service activities, inviting students to pray when a friend is sick or when someone dies, this is to foster empathy, and in the learning process, the teacher applies group learning strategies. Also, schools provide facilities and infrastructure for extracurricular activities such as drum bands, Banjari prayers, and khutbahs, to foster a sense of cooperation or develop relationships with other people.